Hantaviridae: Current Classification and Future Perspectives - Laenen, Lies; Vergote, Valentijn; Calisher, Charles H.; Klempa, Boris; Klingström, Jonas; Kuhn, Jens H.; Maes, Piet (Viruses, 2019)
In recent years, negative-sense RNA virus classification and taxon nomenclature have undergone considerable transformation. In 2016, the new order Bunyavirales was established, elevating the previous genus Hantavirus to family rank, thereby creating Hantaviridae. Here we summarize affirmed taxonomic modifications of this family from 2016 to 2019. Changes involve the admission of >30 new hantavirid species and the establishment of subfamilies and novel genera based on DivErsity pArtitioning by hieRarchical Clustering (DEmARC) analysis of genomic sequencing data. We outline an objective framework that can be used in future classification schemes when more hantavirids sequences will be available. Finally, we summarize current taxonomic proposals and problems in hantavirid taxonomy that will have to be addressed shortly.